2001
DOI: 10.1046/j.1468-3083.2001.00296.x
|View full text |Cite
|
Sign up to set email alerts
|

Vesicular prurigo pigmentosa cured by minocycline

Abstract: We present a case of prurigo pigmentosa associated with vesicles that we call 'vesicular prurigo pigmentosa'. The subject was treated using minocycline with good results and no recurrence of the lesions over a 2-year period.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 4 publications
0
12
0
Order By: Relevance
“…PP has been treated by doxycycline, minocycline and dapsone to good effect; minocycline appears to be more effective than doxycycline and dapsone due to its rapid resolution and fewer adverse side‐effects in treating PP . Indeed, Gironi confirmed that 2 weeks of minocycline treatment can significantly decrease PP skin lesions …”
Section: Discussionmentioning
confidence: 99%
“…PP has been treated by doxycycline, minocycline and dapsone to good effect; minocycline appears to be more effective than doxycycline and dapsone due to its rapid resolution and fewer adverse side‐effects in treating PP . Indeed, Gironi confirmed that 2 weeks of minocycline treatment can significantly decrease PP skin lesions …”
Section: Discussionmentioning
confidence: 99%
“…A variety of agents are used in the treatment of PP, the most effective of which are oral antibiotics such as minocycline, doxycycline and sulfonamides such as dapsone . Recently, minocycline has been preferred to dapsone because it has fewer side‐effects and results in a longer remission . The therapeutic effects of minocycline and doxycycline are thought to be due to their anti‐inflammatory effects.…”
Section: Discussionmentioning
confidence: 99%
“…663 It is uncommon in the Western world, although over 50 cases have now been reported. 666,667,673 Doxycycline, macrolide antibiotics, isotretinoin, 674 and dapsone have also been used to treat this condition. [668][669][670] Its association with Helicobacter infection may have been fortuitous.…”
Section: Dowling-degos Diseasementioning
confidence: 99%